An environmental transition–aware data transmission scheme with energy efficiency in energy harvesting wireless sensor networks. (5th December 2014) - Lee, Kyungrak; Yoo, Jaeyoung; Joe, Inwhee
Various energy harvesting based network technologies have been studied to overcome a limited power resource problem for wireless sensor networks. This paper proposes a new efficient Data Transmission Scheme based on environmental transition awareness in energy harvesting wireless sensor network. Although previous studies proposed a communication protocol for energy harvesting based sensor networks, it still needs additional discussion to improve an efficiency of power consumption. The proposed algorithm controls a data transmission interval whereas considering residual power levels and environmental transition. Through this, the proposed scheme improves the efficiency of power consumption and facilitates continuous operation. The performance evaluation result shows that proposed scheme is more efficient in terms of energy efficiency and increases the network life time compared with previous research.